THE ANALYSIS OF SOCIAL CRITICISM IN MILLAY’S POEM EPITAPH FOR THE RACE OF MAN - Vanesa F. Umboh; Tini Mogea; Paula Rombepajung (KOMPETENSI, 2022)
The purpose of this study is to describe the social criticism in the poem Epitaph for the Race of Man by Edna St. Vincent Millay. In this study, the researchers usequalitative descriptive research method.. This study used sociological approach which is connects fiction in literary works with the existing reality and have a relationship. Data sources in this research is the poem Epitaph for the Race of Man by Edna St. Vincent Millay especially in sequences I,IV,V,X and XI which there are social criticism with indirect form of submission or implicit meaning. From the result of this study, the researcher found social criticism of how humans treat nature by providing an overview of disasters as the impact of human behavior and also seven problems of social criticism: (1) Social criticism of moral problem; (2)Social criticism of economic problems; (3) Social criticism of political problems; (4) Social criticism of technology problems; (5) Social criticism of religious issues; (6) Social criticism of Educational problems; (7) Social criticism of cultural issues. It can be concluded that the poem Epitaph for the Race of Man really contains social criticism.